Twitter e ciberativismo: o movimento social da hashtag #ForaMicarla em Natal-RN - Silva, Raquel Souza da (2012)
The spatial and temporal fluidity conditioned by the technologies of social interaction online have been allowing that collective actions of protest and activism arise every day in cyberspace - the cyber-activism. If before these actions were located in geographical boundaries, today's demands and mobilizations extrapolate the location, connect to the global, and at the same time, return to the regional through digital virtuality. Within this context of the relationship between digital technology and global flow of sociability, emerges in October 2010 the social movement of the hashtag "#ForaMicarla", which means the dissatisfaction of cibernauts from Natal of Twitter with the current management of the municipality of Natal-RN, Micarla de Sousa (Green Party). We can find in the center of this movement and others who appeared in the world at the same time a technological condition of Twitter, with the hashtag "#". Given this scenario, this research seeks to analyze how the relationship of the agents of movement hashtag "ForaMicarla", based on the principle that it was formed in the Twitter network and is maintained on the platform on a daily basis, it can create a new kind of political culture. Thus, this study discusses theoretically the importance of Twitter and movements that emerge on the platform and through it to understand the social and political demands of the contemporary world and this public sphere, which now seems to include cyberspace